2019
DOI: 10.1136/thoraxjnl-2018-211845
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke alters arachidonic acid metabolism and inflammation in infants and children with cystic fibrosis

Abstract: BackgroundMechanisms that facilitate early infection and inflammation in cystic fibrosis (CF) are unclear. We previously demonstrated that children with CF and parental-reported secondhand smoke exposure (SHSe) have increased susceptibility to bacterial infections. SHSe hinders arachidonic acid (AA) metabolites that mediate immune function in patients without CF, and may influence CF immune dysfunction. We aimed to define SHSe’s impact on inflammation mediators and infection in children with CF.MethodsSeventy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…At present, the pro-inflammatory and/or anti-inflammatory effects of PGD 2 are difficult to understand. Although the paper of Kopp et al 2 does not provide a definite answer, it is important to note that not only PGD 2 was downregulated. The manuscript’s findings are especially interesting since CFTR itself seems to be involved in the regulation of the PGD synthase-PGD 2 -15d-PGJ 2 pathway 6…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…At present, the pro-inflammatory and/or anti-inflammatory effects of PGD 2 are difficult to understand. Although the paper of Kopp et al 2 does not provide a definite answer, it is important to note that not only PGD 2 was downregulated. The manuscript’s findings are especially interesting since CFTR itself seems to be involved in the regulation of the PGD synthase-PGD 2 -15d-PGJ 2 pathway 6…”
mentioning
confidence: 94%
“…Taken together, Kopp et al 2 showed for the first time that infants and children with CF and SHS exposure biosynthesize significantly lower amounts of AA-derived lipid mediators, have dysregulated inflammatory gene expression and have impaired bacterial clearance. By correlation of PGD 2 levels with clinical outcome, the authors could show the high impact of altered AA-dependent lipid mediator pathways in infants and children with CF, particularly by SHSe.…”
mentioning
confidence: 94%
See 3 more Smart Citations